A review of the Organisation of American States (OAS) Citizen Security Indicators (CSI) for use in a South African violence, injury and trauma observatory - Jabar, Ardil (Acta criminologica, 2019)
The Organisation of American States (OAS) Citizen Security indicators were launched as a regional agreement in the Americas to bring about the standardisation of citizen security indicators for the region, in order to compare and contrast citizen security related issues. The 22 indicators were agreed upon by member states at the 4th OAS conference in 2012. This is the first attempt to critically review the suitability of the application of the indicators in an African context. The primary objective of this article being to review the OAS CSI for use in the pilot Cape Town Violence, Injury and Trauma Observatory (CT VITO). Research methods employed in this study included a review of all national and provincial violence-related databases so as to locate the citizen security indicators. Violence prevention stakeholders were contacted where indicators were not reported in national or provincial reports. International organisation databases, such as the World Health Organisation (WHO) and the United Nations Office on Drugs and Crime (UNODC), were reviewed where indicators were not reported locally. Delphi is a planned consensus process that utilises a panel of experts to investigate a complex problem, employing a sequence of structured statements. A Delphi study was conducted to allow the opportunity for local experts in injury surveillance and emergency services to comment on the 19 Citizen Security indicators and to determine their inclusion in the pilot observatory. Three indicators were excluded as they were either related to traffic injuries or dealt with child and adolescent injuries, which is not the primary focus of the pilot observatory. The remaining 19 indicators were all found to be viable for inclusion in the pilot CT VITO. Following the Delphi study, 14 indicators reached positive consensus, seven indicators reached negative consensus and nine indicators did not reach consensus. The indicators that reached positive consensus will inform the basic research infrastructure of the pilot VITO, along with datasets and research priorities established by the Delphi study, and may serve as part of a regional standardised data collection to guide the development of other local violence and injury observatories.